A Pre-conceptual-schema-based method for eliciting requirements in the context of ISO/IEC 29110 (2019)
Standards such as the ISO/IEC 29110 have been adopted and practiced by Very Small Entities (VSE) for improving quality of the software process. The basic profile established in the management and engineering guide of such standard includes a set of best practices for enhancing the process in terms of time, efficiency, budget, and documentation. On the other hand, pre-conceptual schemas are knowledge representations created for modeling a domain in a graphical, easy, and intuitive environment. The amount of VSEs adopting the basic profile has increased, since most of the projects developed by VSEs are suitable for this process model. What-to-do is described in detailed standard processes, leaving the how-to-do-it choice at discretion of the organization willing to implement such a standard. Consequently, the processes detailed in the ISO/IEC 29110 lack prescription of a particular method and VSEs face a compliance problem when implementing and developing the standard activities. Such a fact could lead to possible misunderstanding of the standard by VSEs, failing to achieve the expected quality and moving away from the project objectives, especially in first-time implementations. In this M.Sc. Thesis, we propose a method based on the ISO/IEC 29110 for eliciting requirements in very small entities by using executable pre-conceptual schemas. Besides, we validate the proposed method by conducting a case study in a research project financed by a governmental entity. By developing such a method, we intend to consolidate an alternative to VSEs when implementing the basic profile of the ISO/IEC 29110 in early stages.